Shear-bond transfer mechanisms of partial embedment of structural steel section in precast concrete beams - Hu, Heng Bia (2008)
Precast concrete technology is widely used in industry both worldwide and in Singapore. It enhances production quality and expedites the construction. However, the conventional precast concrete still has some shortcomings and therefore a new type of hybrid precast concrete beam is suggested and its behaviour studied. This research is primarily aimed at investigating the internal shear bond mechanism of precast concrete beam embedded with structural steel section and then to establish the design criteria for such precast concrete beam.